Putting a New `Spin' on Energy Information: Measuring the Impact of Reframing Energy Efficiency Information on Tumble Dryer Choices in a Multi-country Experiment - Denny, Eleanor (My University, 2024)
It has been shown that consumers often underinvest in energy efficiency despite net benefits over the longer term. One possible explanation is that they do not properly understand energy information when provided in physical units, as in most energy labels. Prior studies have investigated the effect of reframing energy information into monetary units. Outcomes are mixed, and it is unclear whether this is due to the use of different products, methodologies or to studies being conducted in countries with different energy prices and labelling standards. This paper overcomes this ambiguity by testing the effect of providing monetary energy information using the same experiment in a multi-country setting. Results show that the intervention’s effectiveness varies considerably across countries. Moreover, they highlight the presence of within-country heterogeneities based on demographic characteristics, with monetary information being more effective for high-usage households but seemingly crowding out the motivation of those whose purchasing decisions depend on environmental considerations.
PUBLISHED
Keywords: within-country heterogeneities; energy information; labelling standards; Energy efficiency information; Energy efficiency labels; Discrete choice experiment; Tumble dryers; Framing effect; within-country heterogeneities; energy information; labelling standards; Smart & Sustainable Planet